ANALISIS STILISTIKA PADA PUISI SEGALA, SEGALA KARANGAN SUTAN TAKDIR ALISJAHBANA - Domas Sugrahita Harja Susetya; Safira Hamdala; Moh. Faja Al Hakim (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the style of language in literary criticism for the meaning of literary works. Because the meaning of literary works cannot be separated from the style of language used in the criticized literary works. Researchers collected data through a poem by Sutan Takdir Alisjahbana entitled Segala, Segala. The method used is descriptive qualitative with a stylistic approach, then the data is analyzed using the Miles and Huberman model, namely data reduction (data reduction), data display (data presentation), and conclusion drawing and verification (conclusion and verification. The results found are the use of The diction in it is simple so that it is easy for the reader to understand the meaning of the poem. It also includes the use of figure of speech pleonasm, tautology, personification, hyperbole, and repetition. Meanwhile, in the inner aspect of poetry the author presents it as if the reader is experiencing it. Alisjahbana's destiny chosen by the author contains a style of language to convey its implied message.As a suggestion, in this study data collection using a very simple method, it is very likely that future researchers can use other methods so that the results are more in-depth.